Pemetaan Bisnis Sabun Ecoenzym Produksi Biarawati Ekopastoral DSY Menggunakan Business Model Canvas - Tuju, Natalia Nadia; Montolalu, Maya Hendrietta; Waney, Nordy Fritsgerald Lucky (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2024)
This research aims to map the Ecoenzym soap business model produced by Ecopastoral Dsy nuns using the Business Model Canvas (BMC) at the Dsy Ecopastoral Center in Kawatak village, South Langowan District, Minahasa Regency. The research period was carried out for 3 months, namely from April to June 2024. The data collection method is a descriptive qualitative approach, data collection is a population survey by making direct observations at the research location and distributing prepared questionnaires. The results of the research show that based on the results of the identification, mapping and analysis of business models that have been carried out by researchers, the conclusion that can be drawn is that there are six elements of the canvas model business that need to be improvised into a new canvas business model, including customer relationships, channels, partnerships, key resources, revenue streams and value offered.